2011
DOI: 10.1002/cncr.26525
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of KISS1 protein expression for brain invasion and metastasis

Abstract: BACKGROUND Metastases to the brain represent a feared complication and contribute to the morbidity and mortality of breast cancer. Despite improvements in therapy, prognostic factors for development of metastases are lacking. KISS1 is a metastasis suppressor that demonstrates inhibition of metastases formation in several types of cancer. The purpose of this study was to determine the importance of KISS1 expression in breast cancer progression and the development of intracerebral lesions. METHODS In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…In fact, a significant down-regulation of KISS1 expression has been reported in brain metastatic lesions, compared to primary ductal carcinomas and this correlated with immunohistochemical analysis of KISS1 protein levels64. This suggests that a loss of KISS1 may contribute to the formation of distant metastases, since there was a down-regulation of KISS1 expression in the metastases compared to primary tumors 67. Thus, these studies support the anti-metastatic role of KISS1 52, 67.…”
Section: Kiss1 Expression In Human Breast Tumorssupporting
confidence: 59%
See 1 more Smart Citation
“…In fact, a significant down-regulation of KISS1 expression has been reported in brain metastatic lesions, compared to primary ductal carcinomas and this correlated with immunohistochemical analysis of KISS1 protein levels64. This suggests that a loss of KISS1 may contribute to the formation of distant metastases, since there was a down-regulation of KISS1 expression in the metastases compared to primary tumors 67. Thus, these studies support the anti-metastatic role of KISS1 52, 67.…”
Section: Kiss1 Expression In Human Breast Tumorssupporting
confidence: 59%
“…No association of KISS1 expression was found with genes that regulate cell-cycle and proliferation such as HER2 , VEGF and p53 52. KISS1 mRNA and protein expression was also found to be significantly higher in primary breast cancer compared with breast tumors that metastasized to the brain67, 68. In fact, a significant down-regulation of KISS1 expression has been reported in brain metastatic lesions, compared to primary ductal carcinomas and this correlated with immunohistochemical analysis of KISS1 protein levels64.…”
Section: Kiss1 Expression In Human Breast Tumorsmentioning
confidence: 89%
“…Martin et al (27) reported that KISS1 expression increased with tumor progression and that KISS1R was elevated in invasive ductal tumors, as shown using realtime PCR and immunohistochemistry of human breast tumors. A more recent study demonstrated a positive correlation between the expression of KISS1, with progression of breast cancer, leading the authors to conclude that KISS1 may be used as a prognostic marker for increased risk of breast cancer progression (28). In further agreement, Marot et al (29) reported that among estrogen receptor alpha (ER␣)-positive tumor samples from patients treated with the ER antagonist, tamoxifen, patients with poor prognosis had elevated expression of KISS1 and KISS1R.…”
supporting
confidence: 65%
“…They demonstrated that KiSS1 mRNA and protein expression were increased with increase in tumor grade and in metastatic patients vs control population and that this was associated with poor patient prognosis. Contradictory to Martin's study other reports indicate that KiSS1 mRNA and protein expression were also found to be significantly higher in primary breast cancer compared with breast tumors that metastasized to the brain (Ulasov et al, 2012;Stark et al, 2005). This suggests that a loss of KiSS1 may contribute to the formation of distant metastases, since there was a down-regulation of KiSS1 expression in the metastases compared to primary tumors (Ulasov et al, 2012) Thus, these studies support the antimetastatic role of KiSS1 (Ulasov et al, 2012).…”
Section: Evaluation Of Kiss1 As a Prognostic Biomarker In North Indiansupporting
confidence: 54%
“…Contradictory to Martin's study other reports indicate that KiSS1 mRNA and protein expression were also found to be significantly higher in primary breast cancer compared with breast tumors that metastasized to the brain (Ulasov et al, 2012;Stark et al, 2005). This suggests that a loss of KiSS1 may contribute to the formation of distant metastases, since there was a down-regulation of KiSS1 expression in the metastases compared to primary tumors (Ulasov et al, 2012) Thus, these studies support the antimetastatic role of KiSS1 (Ulasov et al, 2012). The reason for these conflicting results could be a difference in the method of analysis of patient samples, patient inclusion and exclusion criteria such as whether the patients had received chemotherapy, the age of the women (pre-versus post-menopausal) and the different gene pool of the patient subset (Donna et al, 2013).…”
Section: Evaluation Of Kiss1 As a Prognostic Biomarker In North Indianmentioning
confidence: 84%